Rolling e-learning: an educational model to support Italian healthcare professionals during the COVID-19 pandemic - Pregliasco, Fabrizio Ernesto; Valetto, Maria Rosa; Anelli, Filippo; Moretti, Ugo; Scarpa, Nicoletta; Dri, Pietro (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Rolling reviews have been widely used by the scientific community during the COVID-19 pandemic to provide guidelines and identify potential treatments in such a quickly evolving emergency. Throughout the two pandemic years, we provided independent and continuously updated (rolling) e-learning courses on COVID-19 targeted to Italian healthcare professionals with the aim of increasing dissemination based on the emerging evidence. The results of this project are presented in this brief report. Methods: We launched five main courses on COVID-19 – with focus on treatments and vaccines – from February 2020 to December 2022. For each course, we collected and analised participation data and, via questionnaires, customer-satisfaction data on relevance, quality, efficacy and sponsor perception. Results: From 22 February 2020 to 31 December 2022, a total of 224,459 enrollments were registered over the five courses with 192,966 passes (86%), for which Continuing Medical Education (CME) credits were awarded. Over 94% of participants considered the contents of high quality, relevant and effective for their educational needs. The absence of sponsorship perception, 83% overall, decreased relevantly for the two courses on COVID-19 vaccines (68.3%). Conclusions: Italian healthcare professionals working during the pandemic overwhelmingly appreciated and valued the rolling e-learning offer aimed at widening the dissemination of the best practices on COVID-19. This educational model provides independent, evidence-based and tailored information with the undoubted advantages of time flexibility, remote participation and continuous update, all elements that make it a useful tool in a pandemic as well as in a post-pandemic era.